The Contribution of Islamic Capital Markets in the Islamic Economy to Social and Economic Impacts - Furaqanul Amirur Rifan; Taufiqur Rahman (Penerbit Hellow Pustaka, 2026)
The Islamic capital market plays a strategic role in supporting the Islamic economy, not only from a financial perspective but also a social one. This study aims to evaluate the contribution of the Islamic capital market to economic growth and social impact using a Systematic Literature Review (SLR) approach. Data were collected from various databases such as Google Scholar, Scopus, DOAJ, SINTA, and SSRN, based on relevant articles published between 2016 and 2023. The results show that the Islamic capital market contributes to financing the real sector, increasing financial inclusion, and promoting equitable welfare distribution. However, challenges such as low financial literacy and a lack of product innovation remain significant obstacles. This study highlights the need for educational strategies and sustainable policies to maximize the potential of the Islamic capital market in advancing the Islamic economy.